“Lapar Mata”: Mahasiswi, Kecantikan, dan Perilaku Konsumtif - Fitria Rahma Juliana (Emik, 2022)
Beauty is something that is coveted by women, including female students. The image of woman has long been known as a beautiful creature and is synonymous with beauty. For female students themselves, fashion, appearance, and beauty are important aspects that get special attention, so they spend a lot of money for the purpose of buying beauty products. This article focuses on how female students embody beauty social standards related that cause them to behave consumptively. This qualitative research was conducted in the city of Makassar, involving 14 female students of Hasanuddin University Makassar. They are between 18 and 23 years old. Data was collected through in-depth interviews and observations on social media, such as Youtube, Instagram, and Tiktok. The study indicates that in the view of female students there are two concepts of beauty, namely physical beauty (outer beauty) and non-physical beauty (inner beauty). Beauty products were chosen on the basis of product content and/or influenced by reviews, both reviews from social media and reviews from friends. In the use of beauty products, female students tend to behave consumptively because of the variety of treatments and products used, the desire to appear different from the others, the desire to get recognition from others in order to attract others’ attention, or just following others. It is argued in this article that the tendency of female students to behave consumptively is because their needs is overpowered by their desires, such behavious is locally termed as “lapar mata”.